Transformation Of Pesantren Education Management In The Digital Era (Analysis Of Tradition Adaptation Through Educational Innovation Theory) - Kusuma, Muh. Thoriq Aziz; Muharom, Fauzi; Jandra, Mifedwil (MID Publisher International, 2025)
Pesantren (Islamic Boarding School) as a traditional Islamic educational institution faces major challenges in navigating changes in the digital era. This study aims to analyze how pesantren transform while maintaining traditional values ​​using the educational innovation theory approach. This research method is qualitative with a literature study approach that utilizes related literature. The results of the study indicate that the transformation of pesantren education management in the digital era includes digitalization of administration, development of online-based learning platforms, and increasing human resource competencies. The application of educational innovation theory is key to supporting the adaptation of tradition to a modern context. This study provides strategic recommendations for pesantren to develop a digital-based management ecosystem that still respects Islamic values.